Odpowiedź :
a)
[tex]f(x)=x^2-3x+2\\a=1,\ b=-3,\ c=2[/tex]
postać iloczynowa:
[tex]\Delta=b^2-4ac=(-3)^2-4*1*2=9-8=1\\\sqrt\Delta=1\\x_1=\frac{-b-\sqrt\Delta}{2a}=\frac{3-1}{2}=1\\x_2=\frac{-b+\sqrt\Delta}{2a}=\frac{3+1}{2}=2\\f(x)=a(x-x_1)(x-x_2)\\f(x)=(x-1)(x-2)[/tex]
postać kanoniczna:
[tex]p=-\frac{b}{2a}=-\frac{-3}{2*1}=\frac{3}{2}\\q=-\frac{\Delta}{4a}=-\frac{1}{4*1}=-\frac{1}{4}\\f(x)=a(x-p)^2+q\\f(x)=(x-\frac{3}{2})^2-\frac{1}{4}[/tex]
przedziały monotoniczności:
ramiona są do góry, bo a jest dodatnie, więc
[tex]f\searrow\text{ dla }x\in\left(-\infty,\frac{3}{2}\right > \\f\nearrow\text{ dla }x\in\left < \frac{3}{2},+\infty\right)[/tex]
b)
[tex]f(x)=(x-\frac{1}{2})^2-3[/tex]
postać kanoniczna:
[tex]f(x)=(x-\frac{1}{2})^2-3[/tex]
postać iloczynowa:
[tex]f(x)=(x-\frac{1}{2})^2-3=(x-\frac{1}{2}-\sqrt3)(x-\frac{1}{2}+\sqrt3)[/tex]
Uwaga: Skorzystałem ze wzoru skróconego mnożenia na różnicę kwadratów.
przedziały monotoniczności:
ramiona są do góry, bo a jest dodatnie, więc
[tex]f\searrow\text{ dla }x\in\left(-\infty,\frac{1}{2}\right > \\f\nearrow\text{ dla }x\in\left < \frac{1}{2},+\infty\right)[/tex]